1984
DOI: 10.1002/hep.1840040107
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine: A Model Compound for Measuring Liver Function

Abstract: The effects of liver disease on caffeine plasma clearance (Cl) and on exhalation of 14CO2 following i.v. injection of 2 mu Ci of [3-methyl-14C]caffeine together with 125 mg of the unlabeled compound were measured in 15 patients with cirrhosis, 11 subjects with miscellaneous liver disease, and 10 normal volunteers. Compared to mean values for Cl (2.02 +/- S.D. 0.68 ml per min per kg) and t1/2 (3.8 +/- 0.9 hr) in normal volunteers, cirrhotics were characterized by highly significant reductions in Cl (to 0.76 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
60
0
3

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(71 citation statements)
references
References 17 publications
8
60
0
3
Order By: Relevance
“…It has been suggested that caffeine concentrations in the plasma after an overnight fast (Renner et al, 1984) or else plasma concentrations determined 12 h after an oral caffeine load (Wang et al, 1985) might serve as a simple guide to the severity of hepatic dysfunction. In the present study, basal serum and salivary caffeine concentrations after 72 h without caffeine were higher in our patients with liver disease than in the control subjects, but only three patients with decompensated cirrhosis had values in excess of 2 mg l-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that caffeine concentrations in the plasma after an overnight fast (Renner et al, 1984) or else plasma concentrations determined 12 h after an oral caffeine load (Wang et al, 1985) might serve as a simple guide to the severity of hepatic dysfunction. In the present study, basal serum and salivary caffeine concentrations after 72 h without caffeine were higher in our patients with liver disease than in the control subjects, but only three patients with decompensated cirrhosis had values in excess of 2 mg l-1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it has been shown that plasma caffeine clearance is significantly reduced in patients with cirrhosis and its elimination half-life is significantly prolonged (Desmond et al, 1980;Wietholtz et al, 1981;Renner et al, 1984;Wang et al, 1985). Although caffeine loading tests are inexpensive, simple to perform and safe, the test procedure has yet to be standardised and there are few guidelines as to how the test results should be interpreted.…”
Section: Introductionmentioning
confidence: 99%
“…For equivalent intravenous doses of the methylxanthines administered to rats, the plasma clearances and half-lives of PX and CA were similar whereas the plasma clearances of TP and TB were approximately half that for PX and the half-lives of TP and TB were approximately double that of PX. The pharmacokinetic parameters of CA, TP and TB determined in this study are similar to those generally reported in the literature (Birkett etal., 1982(Birkett etal., ,1985Blanchard & Sawers, 1983a;Bonati et al, 1982;Ogilvie, 1978;Renner et al, 1984;Tarka et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A number of methods or drug clearance evaluations have been reported to estimate human liver function (Roberts et al 1978, Homeida et al 1979, Baker et al 1983, Renner et al 1984. The use of drugs as liver function indicators may increase the burden on liver cells, as well as a certain degree of damage.…”
mentioning
confidence: 99%